The effect of exercise intensity on exercise‐induced hypoalgesia in cancer survivors: A randomized crossover trial. Issue 19 (4th October 2021) - Clifford, Briana K.; Jones, Matthew D.; Simar, David; Barry, Benjamin K.; Goldstein, David
Abstract: Pain is experienced by people with cancer during treatment and in survivorship. Exercise can have an acute hypoalgesic effect (exercise‐induced hypoalgesia; EIH) in healthy individuals and some chronic pain states. However, EIH, and the moderating effect of exercise intensity, has not been investigated in cancer survivors. This study examined the effect of low‐ and high‐intensity aerobic exercise on EIH in cancer survivors after a single exercise session as well as a brief period of exercise training (2‐weeks, three exercise sessions per week). Participants ( N  = 19) were randomized to low‐ (30%–40% Heart Rate Reserve (HRR) or high‐ (60%–70% HRR) intensity stationary cycling for 15–20 min. Pressure pain thresholds (PPT) were assessed over the rectus femoris and biceps brachii before and after a single exercise session and again after a short training period at the assigned intensity. Then, following a 6‐week washout period, the intervention was repeated at the other intensity. After the first exercise session, high‐intensity exercise resulted in greater EIH over the rectus femoris than low intensity (mean difference ± SE: −0.51 kg/cm 2  ± 0.15, Cohen's d  = 0.78, p  = 0.004). After a 2‐week training period, we found no difference in EIH between intensities (0.01 kg/cm 2  ± 0.25, d  = 0.00 p  = 0.99), with comparable moderate effect sizes for both low‐ and high‐intensity exercise, indicative of EIH. No EIH was observed over the biceps brachii of the arm at either low or high intensity. Low‐intensity exercise training may be a feasible option to increase pain thresholds in cancer survivors. Abstract : High‐intensity exercise increased pressure pain thresholds more than low‐intensity exercise over the exercising muscle of the leg. However, after a short training period, there was no difference between low‐ and high‐intensity exercise on pain thresholds, with both intensities eliciting a hypoalgesic effect. These results suggest that both low‐ and high‐intensity exercise training may be effective at increasing pain thresholds in cancer survivors.